2020
DOI: 10.3897/neobiota.63.57925
|View full text |Cite
|
Sign up to set email alerts
|

Native and non-native sources of carbohydrate correlate with abundance of an invasive ant

Abstract: Invasive species threaten many ecological communities and predicting which communities and sites are invasible remains a key goal of invasion ecology. Although invasive ants often reach high abundances in association with plant-based carbohydrate resources, the source and provenance of these resources are rarely investigated. We characterized carbohydrate resources across ten sites with a range of yellow crazy ant abundance in Arnhem Land, Australia and New Caledonia to determine whether yellow crazy ant (Anop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…2); thus, the symbiont compositions could serve as an indicator for the nest or re ect possible supercolony relationships, at least at ne geographic scales [36]. To the best of our knowledge, the current study revealed the intra-nest dynamics of the symbionts associated with A. gracilipes colonies for the rst time; such information is key to understanding the effects of these symbionts on possible adaptations and physiological reactions in A. gracilipes [4].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…2); thus, the symbiont compositions could serve as an indicator for the nest or re ect possible supercolony relationships, at least at ne geographic scales [36]. To the best of our knowledge, the current study revealed the intra-nest dynamics of the symbionts associated with A. gracilipes colonies for the rst time; such information is key to understanding the effects of these symbionts on possible adaptations and physiological reactions in A. gracilipes [4].…”
Section: Discussionmentioning
confidence: 89%
“…The sampling times for the Southern Hemisphere all fell within October-November and late spring to early summer; for sampling in the Northern Hemisphere, especially in the current study, the wooden boxes were sampled from June to September, i.e., during the summer period. Sampling in different seasons might therefore have interfered with the pattern of Wolbachia infection in A. gracilipes [4,8]. Furthermore, individual sites had infestations ranging in size from 10 to 50 km 2 , and between 2 and 61 ants from each site were screened by Sebastien et al [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Standardised highest yellow crazy ant abundance reported within fourteen studies as calculated by the relationships between the three sampling methods of card counts, pitfall trapping and tuna lures using a) summed log(x+1)-transformed sample data, and b) log(x+1)-transformed pooled data. Studies are: 1) [ 30 ]; 2) [ 31 ] New Caledonia site; 3) [ 31 ] Australia site; 4) [ 21 ]; 5) [ 32 ]; 6) this study; 7) [ 33 ]; 8) [ 34 ] 9) [ 17 ]; 10) [ 35 ]; 11) [ 36 ]; 12) [ 37 ]; 13) [ 38 ]; and 14) [ 3 ]. …”
Section: Resultsmentioning
confidence: 99%